Analisis Proses Penanganan Penyalahguna Narkotika di BNN Kota Surabaya: Studi Kasus Sopir Ekspedisi yang Menggunakan Narkotika Sebagai Doping - Lumbanraja, Christian Felix; Arianti, Nita (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2025)
The handling of narcotics abuse cases in Indonesia, especially those involving an expedition driver who uses drugs for work, requires special attention from the National Narcotics Agency (BNN). This study aims to analyze the process of handling narcotics abuse by expedition spires in BNN Surabaya City starting with a focus on the legal process, factors that encourage drug use at work, and the role of BNN in rehabilitation and recovery. The method used is a qualitative approach with interviews and documentation studies as data collection tools. The results of the study showed that people involved in drug abuse were often caught up in job pressures that required them to use drugs as physical and mental stimulants. BNN Surabaya City has carried out handling procedures involving investigation, rehabilitation, and legal assistance. But the biggest challenge is the lack of awareness of the dangers of drugs among workers in the transportation sector. This study provides important insights into the importance of preventive and rehabilitative approaches in overcoming narcotics abuse involving drivers.